2019
DOI: 10.1158/1535-7163.mct-18-0417
|View full text |Cite
|
Sign up to set email alerts
|

Necuparanib, A Multitargeting Heparan Sulfate Mimetic, Targets Tumor and Stromal Compartments in Pancreatic Cancer

Abstract: Pancreatic cancer has an abysmal 5-year survival rate of 8%, making it a deadly disease with a need for novel therapies. Here we describe a multitargeting heparin-based mimetic, necuparanib, and its antitumor activity in both in vitro and in vivo models of pancreatic cancer. Necuparanib reduced tumor cell proliferation and invasion in a three-dimensional (3D) culture model; in vivo, it extended survival and reduced metastasis. Furthermore, proteomic analysis demonstrated that necuparanib altered the expression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…In addition to roneparastat, HS mimetics muparfostat (PI-88) (233), neuparanib (N-402) (234), piixatimod (PG545) (251), have been, or are currently in clinical trials for use as a therapy targeting metastasis of melanoma or pancreatic cancer. More recent reports have detailed the use of these HS mimetics not only in the development of therapeutics, but the development of more representative models for testing anticancer/anti-metastatic therapeutics including patient-derived xenografts (237) and organoid models (238). Neuparanib has been shown to reduce tumor cell proliferation and invasion in an organoid model, and plasma levels of patients within a clinical trial cohort reported increased levels of tissue inhibitor of MMP-3 (238).…”
Section: Therapeutic Targeting Of Heparan Sulfate Proteoglycans and Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to roneparastat, HS mimetics muparfostat (PI-88) (233), neuparanib (N-402) (234), piixatimod (PG545) (251), have been, or are currently in clinical trials for use as a therapy targeting metastasis of melanoma or pancreatic cancer. More recent reports have detailed the use of these HS mimetics not only in the development of therapeutics, but the development of more representative models for testing anticancer/anti-metastatic therapeutics including patient-derived xenografts (237) and organoid models (238). Neuparanib has been shown to reduce tumor cell proliferation and invasion in an organoid model, and plasma levels of patients within a clinical trial cohort reported increased levels of tissue inhibitor of MMP-3 (238).…”
Section: Therapeutic Targeting Of Heparan Sulfate Proteoglycans and Tmentioning
confidence: 99%
“…More recent reports have detailed the use of these HS mimetics not only in the development of therapeutics, but the development of more representative models for testing anticancer/anti-metastatic therapeutics including patient-derived xenografts (237) and organoid models (238). Neuparanib has been shown to reduce tumor cell proliferation and invasion in an organoid model, and plasma levels of patients within a clinical trial cohort reported increased levels of tissue inhibitor of MMP-3 (238). The attempt at mimicking the structure of HS has seen the development of glycopolymers with well-defined sulfation patterns and the ability to optimize disaccharide length for peak heparanase inhibition (252), which reduced metastasis of breast cancer in a rodent model.…”
Section: Therapeutic Targeting Of Heparan Sulfate Proteoglycans and Tmentioning
confidence: 99%
“…Analysis of plasma samples of patients with metastatic pancreatic cancer enrolled in a phase I/II study show that treatment with necuparanib in addition to the standard of care significantly increased TIMP3 plasma protein levels confirming the in vivo and in vitro studies on pancreatic cancer models [171]. PG545 has been selected over the PG500 series of heparan sulfate mimetics for the ability to inhibit both angiogenesis and heparanase activity and was selected as the lead clinical candidate for oncology [191].…”
Section: Clinical Considerationsmentioning
confidence: 81%
“…Glycol-splitting of unsubstituted uronic acids obtained by periodate oxidation and borohydride reduction has been applied to a variety of heparin derivatives and increased the flexibility of the molecules for a better interaction and inhibition of heparanase or growth factors. M402 (Necuparanib) is a glycol-split LMWH with reduced anticoagulant activity [170] that was found to reduce tumor burden in vivo in KPFMC pancreatic cancer mice model at a dose of 40 mg/kg/day and reduce AsPC-1 pancreatic cancer cell line proliferation and invasion in vitro in a 3D-culture model [171]. Boothello et al synthesized a non-saccharide compound, G2.2, which is structurally homogeneous and easy to obtain by chemical synthesis, as a mimetic of an HS hexasaccharide active on cancer stem cells.…”
Section: Targeting the Tumormentioning
confidence: 99%
See 1 more Smart Citation